Palaskhshar ointment in the management of Abhyantar Gudarsh – An Ayurvedic Management Protocol (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Hemorrhoids or piles are a common ailment among adults. More than half of men and womenaged 50 years and older will develop hemorrhoid symptoms during their lifetime. This disease Gudarshacomes under the heading of Mahagada, as it is Dirghakalanubandhi, Dushchikitsya in nature, Tridoshaj andinvolves the Marma and it is well known for the chronicity and difficult to treat. Aim & Objectives:- Toevaluate the effect of local application of Palash Kshar Ointment in Management of Abhyantar Gudrsha.Methodology:- The study is prospective randomized controlled clinical trial. Total 60 patients will beselected for this study, which will be further divided randomly into two groups. Each group consists ofabout 30 patients. In which group A, will be trial groups and group B will be control groups. Every patientwill be observed at regular follow up. On 7th, 14th, 21th, 28th Day.. Results– Results will be drawn from theobservations of objective parameters. Conclusion – Conclusion of the study will be drawn on the basis ofstatistical data calculated from the collected data.